Aligning MSMEs with the Triple Bottom Line: A Systematic Literature Review on Sustainable Business Implementation in Indonesia - Wahyudi, Tri; Prasetiyo, Annisa Alya Safira Putri; Wulandari, Siti Sri; Artanti, Yessy (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) contribute 61% to Indonesia’s GDP, yet struggle to adopt the Triple Bottom Line (TBL) framework balancing environmental, social, and economic dimensions. Barriers include limited capital, technological access, and insufficient policy support. This study addresses a critical research gap by systematically analyzing TBL implementation dynamics in Indonesian MSMEs through a Systematic Literature Review (SLR) of 72 Scopus, Sinta 1-2, and nationally accredited articles (2014–2024). Thematic analysis of keywords like “MSMEs,” “TBL,” and “inclusive business” reveals two theoretical contributions: (1) stakeholder collaboration (e.g., partnerships with firms like GoTo and Telkom) bridges resource gaps through digital training and IoT-driven agriculture, and (2) localized inclusive models synergize indigenous practices with innovation to enhance resilience. Practically, the findings advocate for three policy interventions: (1) green fiscal incentives (tax breaks for eco-certified MSMEs), (2) subsidized IoT adoption, and (3) public-private mentorship programs to scale shared-value initiatives. For policymakers, this underscores the urgency to revise national MSME sustainability roadmaps by embedding sector-specific regulations and democratizing access to green technologies via digital platforms. The study also positions MSMEs as pivotal actors in Indonesia’s low-carbon transition, aligning their strategies with SDGs 8 (Decent Work), 9 (Industry Innovation), and 12 (Responsible Consumption). By demonstrating how collaboration and localized innovation overcome structural barriers, this research offers a replicable framework for emerging economies. It redefines MSMEs beyond economic agents to sustainability catalysts, advocating holistic governance that integrates grassroots wisdom with global sustainability agendas. These insights empower governments, businesses, and stakeholders to transform challenges into strategic opportunities, ensuring inclusive growth while advancing planetary well-being.